Impact of Antiretroviral Agents on Blood Cell Parameters - Onukak, E.E. *, Onukak, A.E. , Akwiwu, E.C. , Akpotuzor, J.O. (Sokoto Journal of Medical Laboratory Science)
Human immunodeficiency virus infection continues to be a major public health challenge in under-developed regions due to poverty, war and illiteracy. In developed countries, where much success has been achieved in fighting the menace, access to improved therapy is largely responsible. Nevertheless, studies have linked HIV and antiretroviral therapy with increased risk of cytopenia of all major blood cell lines and associated morbidities such as anaemia and platelet-driven cardiovascular events. Some antiretroviral agents such as zidovudine are associated with bone marrow suppression and an increased risk of developing anaemia Stavudine, azidothymidine and lamivudine have been linked with macrocytic anaemia in patients taking them. Lamivudine in combination with zidovudine causes neutropenia, anaemia and thrombocytopenia. Nevirapine causes eosinophilia, granulopenia and increased enzyme activities. Abacavir sulphate has been linked with increased risk of platelet-driven cardiovascular complications. The advocacy for combined therapy has helped to curb the effects of these agents when taken individually. Prolonged use of highly active antiretroviral therapy has been shown to correct some of these cytopenias and their associated morbidities. In managing HIV-infected patients however regular monitoring of their blood cell parameters and CD4+ count is required to ascertain the efficacy of the regimen being used in treatment.